Non-communicable disease burden among inpatients at a rural district hospital in Malawi - Peter Olds; Chiyembekezo Kachimanga; George Talama; Bright Mailosi; Enoch Ndarama; Jodie Totten; Nicholas Musinguzi; Dickson Hangiwa; Gene Bukhman; Emily B. Wroe (Global Health Research and Policy, 2023)
Abstract Background The burden of non-communicable diseases (NCDs) is high in Malawi. However, resources and training for NCD care remain scarce, especially in rural hospitals. Current care for NCDs in the developing world focuses on the WHO’s traditional 4 × 4 set. However, we do not know the full burden of NCDs outside of that scope, like neurological disease, psychiatric illness, sickle cell disease, and trauma. The goal of this study was to understand the burden of NCDs among inpatients in a rural district hospital in Malawi. We broadened our definition of NCDs beyond the traditional 4 × 4 set of NCDs, and included neurological disease, psychiatric illness, sickle cell disease, and trauma. Methods We conducted a retrospective chart review of all inpatients who were admitted to the Neno District Hospital between January 2017 and October 2018. We broke patients down by age, date of admission, type, and number of NCD diagnoses, and HIV status, and constructed multivariate regression models for length of stay and in-hospital mortality. Results Of 2239 total visits, 27.5% were patients with NCDs. Patients with NCDs were older (37.6 vs 19.7 years, p < 0.001) and made up 40.2% of total hospital time. We also found two distinct populations of NCD patients. The first were patients 40 years and older with primary diagnoses of hypertension, heart failure, cancer, and stroke. The second were patients under 40 years old with primary diagnoses of mental health conditions, burns, epilepsy, and asthma. We also found significant trauma burden, accounting for 40% of all NCD visits. In multivariate analysis, carrying a medical NCD diagnosis was associated with longer length of stay (coefficient 5.2, p < 0.001) and a higher risk of in-hospital mortality (OR 1.9, p = 0.03). Burn patients also had significantly longer length of stay (coefficient 11.6, p < 0.001). Conclusions There is a significant burden of NCDs in a rural hospital in Malawi, including those outside of the traditional 4 × 4 set. We also found high rates of NCDs in the younger population (under 40 years of age). Hospitals must be equipped with adequate resources and training to meet this burden of disease.